INPUT DATA REQUIRED FOR THE TECHNICAL INVESTIGATION OF THE CAUSES OF FIRE AND EXPLOSION INCIDENTS DURING TANK TRUCK LOADING/UNLOADING OF PETROLEUM PRODUCTS: METHODOLOGICAL GUIDELINES (PART 2) - I. Taubkin (Теория и практика судебной экспертизы, 2015)
.